Socio-economic Inequalities in Child Health in Ireland - Nolan, Anne; Layte, Richard (The Economic and Social Review, 2014)
In the literature on the links between socio-economic status (SES) and child health, there is evidence that the SES gradient is weaker for objective indicators of child health (e.g., height) than for subjective indicators (e.g., parental-assessed health). In this paper, we use crosssectional micro-data from the Growing Up in Ireland study to examine the SES gradient in height, weight, general health status and chronic illness incidence. Using household income and mother’s education as indicators of SES, we find only limited support for the contention that the SES gradient in child health in Ireland is stronger for more subjective indicators of child health.